The Effect of Size and Taper of Apical Preparation in Reducing Intra-Canal Bacteria: A Quantitative SEM Study - Mohammadzadeh Akhlaghi, Nahid; Rahimifard, Nahid; Moshari, Amirabbas; Vatanpour, Mehdi; Darmiani, Soheila (Iranian Endodontic Journal, 2013)
Introduction: Bacteria and their byproducts are major etiologic factors in endodontic diseases. Prevention or reduction of root canal bacterial contamination is the main aim of endodontic treatment. The purpose of this in vitro study was to evaluate the effect of size and taper of master apical file (MAF) in reducing bacteria from the apical third of the curved canals using a quantitative scanning electron microscope (SEM) study. Methods and Materials: Eighty-nine human mandibular first molars with curved MB canals (20º-35º) were divided into one control group (n=5) (without rotary instrumentation) and 6 experimental groups (n=14). The canals were prepared using RaCe rotary files to the MAF sizes 25/0.04, 25/0.06, 30/0.04, 30/0.06, 35/0.04 and 35/0.06, in groups 1 to 6, respectively. All the experimental groups were finally rinsed with 2 mL of 17% EDTA followed by 3 mL of 5.25% NaOCl. The mesial roots were split longitudinally. Remaining bacteria in the apical third of MB canals were evaluated using SEM (2000×). Data analysis was performed using one way ANOVA with Tukey’s post hoc test. The level of significance was set at 0.05. Results: All the experimental groups showed significant bacterial reduction (P<0.001). Although the greater size and/or taper resulted in decrease in bacteria, differences between the groups were not significant. Conclusion: Based on this in vitro study the MAF #25/0.04 had no significant difference compared to other groups with greater apical size/taper; all groups could effectively reduce intra-canal bacteria.